Facing the crisis: risk of a collapse or new opportunities? The ISS case study - Toni, Franco (Qualitative and Quantitative Methods in Libraries, 2017)
With the outbreak of the economic crisis, which began  5 years ago, libraries have faced the need to reconsider their role and services. The strong reduction of their budgets, particularly evident (but not only) in the countries of the Mediterranean area, caused a significant decline in terms of performance and available resources for users. This paradigm forced the librarians to redesign their activity in order to find new strategies and solutions that ensure an acceptable quality level of services offered by the library. The speech analyzes the path of the Istituto Superiore di Sanità’s Library (the Italian National Health Institute) for obtaining a rationalization of journals subscriptions, strengthening of cooperation strategies and implementation of new projects and services.